Love of seven dolls - Gallico, Paul, 1897-1976 (Doubleday, 1954)
A young girl called Mouche is about to throw herself into the Seine, when her attention is attracted by a voice. It turns out to be the voice of a glove puppet, called Carrot Top. She then meets Reynard the fox, Gigi, Alifanfaron, Dr Duclos, Madame Muscat and Monsieur Nicholas. The story is about her relationship with the seven puppets and their grim puppetmaster, Capitaine Coq, and what happens when she joins their travelling show.